Assessment of Non-Volant Small Mammals at Lenggor Forest Reserve and Mersing Forest Reserve in Johor, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Surveys of non-volant small mammals were conducted in two fragmented forest reserves within Johor, namely Mersing Forest Reserve (MFR) and Lenggor Forest Reserve (LFR), which are part of the J-PL1 ecological corridor under the Central Forest Spine (CFS) initiative. The surveys were conducted from June to October 2024 to document the diversity of non-volant small mammals at the MFR and LFR. In each forest reserve, six transect lines measuring 100m in length were established at distances of 300m, 500m, and 1000m from the forest edge. Ten collapsible cage traps were set along each transect line and operated for five consecutive nights per session. A total of four sampling sessions were conducted at each site. Apart from this, observation was made to document arboreal species. Overall, 15 species are recorded from both forest reserves. MFR recorded 15 species (six families), while LFR recorded 11 species (four families). Species diversity (Shannon-Wiener Index) is comparable between MFR (H′ = 1.658) and LFR (H′ = 1.635). Notably, two Vulnerable species, namely Maxomys whiteheadi and Maxomys rajah, were also documented at both forest reserves. These findings portray the ecological significance of LFR and MFR as vital habitats that support a diverse community of non-volant small mammals. Hence, maintaining and enhancing habitat connectivity within the J-PL1 corridor is crucial for preserving ecological integrity and ensuring the long-term survival of non-volant small mammal populations in this ecological corridor and its adjacent areas.
Keywords: small mammals; ecological corridor; Peninsular Malaysia; diversity; conservation